Current outcomes in islet versus solid organ pancreas transplant for β-cell replacement in type 1 diabetes. Issue 4 (August 2016) - Wisel, Steven A.; Braun, Hillary J.; Stock, Peter G.
Abstract : Purpose of review: With continued optimization of islet isolation and immunosuppression protocols, the medium-term rates of insulin independence following islet transplantation have improved significantly. This review evaluates the most up-to-date outcomes data for both solid organ pancreas and islet transplantation to develop an algorithm for selection of β-cell replacement in type 1 diabetes patients. Recent findings: Solid organ pancreas and islet transplantation have both displayed improved rates of 5-year insulin independence, largely attributable to improvements in immunosuppressive regimens. The medium-term rates of insulin independence following islet transplantation in highly selected type 1 nonuremic diabetic recipients is beginning to approach the success rates observed following solitary pancreas transplantation. Summary: Although pancreas transplantation has historically been favored for β-cell replacement, current outcomes following islet transplantation justify the use of this minimally invasive therapy in carefully selected patients. Pancreas transplant remains the procedure of choice for β-cell replacement in uremic patients. Islet transplantation should be considered in nonuremic patients with low BMI and low insulin requirements, patients lacking the cardiovascular reserve to undergo open abdominal surgery, or patients who elect to forego the risks of a major operation in exchange for an increased risk of islet graft failure.